THE APPLICATION OF THE MULTI-OBJECTIVE OPTIMIZATION ON THE BASIS OF SIMPLE RATIO ANALYSIS METHOD IN A DECISION SUPPORT SYSTEM FOR PROSPECTIVE UBT STUDENT ASSOCIATION CHAIR CANDIDATES - Pradana, Awang; Fadllullah, Arif; Prasetya, Agung; Fadliansyah, Fadliansyah (STKIP PGRI Tulungagung, 2025)
Decision Support Systems (DSS) have become essential tools in the de-cision-making process across various fields. In the context of selecting the chairman of the Computer Engineering Student Association at Uni-versitas Borneo Tarakan, the use of DSS is also highly relevant and beneficial. The MOOSRA (Multi-Objective Optimization on the basis of Ratio Analysis) method has been chosen as the approach to implement this decision support system. This study aims to apply the MOOSRA method in the implementation of a web-based decision support system for the selection of prospective chairpersons of the Computer Engineer-ing Student Association at Universitas Borneo Tarakan. The MOOSRA method is utilized to consider several criteria, such as leadership skills, communication abilities, dedication, and organizational experience. In this research, the use of MOOSRA is combined with web technology to enhance the efficiency and quality of the candidate selection process. The MOOSRA method offers a structured and objective approach to evaluating candidates for the chairmanship. This approach involves ratio analysis and multi-objective optimization to produce better out-comes. The results of this study are expected to facilitate a fairer and more objective selection process, as well as to improve student satisfac-tion within the Computer Engineering Student Association at Universi-tas Borneo Tarakan.